2009
DOI: 10.1371/journal.pone.0004449
|View full text |Cite
|
Sign up to set email alerts
|

The Integrin Antagonist Cilengitide Activates αVβ3, Disrupts VE-Cadherin Localization at Cell Junctions and Enhances Permeability in Endothelial Cells

Abstract: Cilengitide is a high-affinity cyclic pentapeptdic αV integrin antagonist previously reported to suppress angiogenesis by inducing anoikis of endothelial cells adhering through αVβ3/αVβ5 integrins. Angiogenic endothelial cells express multiple integrins, in particular those of the β1 family, and little is known on the effect of cilengitide on endothelial cells expressing αVβ3 but adhering through β1 integrins. Through morphological, biochemical, pharmacological and functional approaches we investigated the eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
114
4

Year Published

2010
2010
2016
2016

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 121 publications
(128 citation statements)
references
References 51 publications
10
114
4
Order By: Relevance
“…Taken together, we conclude that cilengitide triggered a decrease in blood volume (assessed by the amplitude A) due to smaller and partly nonfunctional blood vessels and increased vessel permeability (assessed by the exchange rate constant k ep ) was observed due to the increased number of immature vessels that arose after treatment with cilengitide. Increased vessel permeability as seen in our study was previously reported by Alghisi et al, 46 who reported VE-cadherin delocalization from cell-cell contact sites on cilengitide treatment leading to a loss of cellular contacts and an increase of endothelial monolayer permeability. In bone metastases, this effect might improve local drug delivery to these lesions when combining cilengitide with standard treatments such as bisphosphonates or chemotherapy.…”
Section: Cancer Therapysupporting
confidence: 90%
“…Taken together, we conclude that cilengitide triggered a decrease in blood volume (assessed by the amplitude A) due to smaller and partly nonfunctional blood vessels and increased vessel permeability (assessed by the exchange rate constant k ep ) was observed due to the increased number of immature vessels that arose after treatment with cilengitide. Increased vessel permeability as seen in our study was previously reported by Alghisi et al, 46 who reported VE-cadherin delocalization from cell-cell contact sites on cilengitide treatment leading to a loss of cellular contacts and an increase of endothelial monolayer permeability. In bone metastases, this effect might improve local drug delivery to these lesions when combining cilengitide with standard treatments such as bisphosphonates or chemotherapy.…”
Section: Cancer Therapysupporting
confidence: 90%
“…Although many studies indicate that synthetic RGD-containing peptides inhibit angiogenesis and tumor growth, our findings provide the first evidence that macrophages may generate and release an RGDKGE-containing collagen epitope that may exhibit pro-angiogenic activity. Importantly, previous studies have suggested that certain RGD peptides can activate ␣v␤3 (58,59) and may enhance vascular permeability (45,57), which might lead to release of inflammatory factors, which in turn may contribute to the formation of new blood vessels.…”
Section: Discussionmentioning
confidence: 99%
“…7, E and F). Activation of Src and p38 MAPK can lead to enhanced actin polymerization and stress fiber formation (43)(44)(45); therefore, we examined the actin cytoskeleton in endothelial cells following binding to the RGD collagen peptides. Interestingly, endothelial cell interactions with the RGD-KGE collagen peptide P-2 resulted in accelerated actin stress fiber formation as a statistically significant increase in the percentage of cells with actin stress fibers were observed in endothelial cells attached to P-2 (RGDKGE) as compared with interactions with P-1 (RGDAPG) peptide (Fig.…”
Section: Journal Of Biological Chemistrymentioning
confidence: 99%
“…This would partially explain why Fibrinogen Caracas VIII with normal αC had less interaction with the cells. The contribution of fibrin binding to VE-cadherin to fibrin organization is less clear, since the VE-cadherin contributes to cell-cell and not to cell-extracellular matrix interaction [27].…”
Section: Resultsmentioning
confidence: 99%